2021
DOI: 10.1016/j.athoracsur.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-term Outcome of Minimally Invasive Direct Coronary Artery Bypass

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Patients in the MIDCAB group had less blood transfusion, lower postoperative Troponin peak values, and shorter time on ventilator, and lower need for surgical revisions than the FS-OPCAB group. These findings are consistent with other studies (18,19). Notably, in our series there was no perioperative mortality in the MIDCAB group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients in the MIDCAB group had less blood transfusion, lower postoperative Troponin peak values, and shorter time on ventilator, and lower need for surgical revisions than the FS-OPCAB group. These findings are consistent with other studies (18,19). Notably, in our series there was no perioperative mortality in the MIDCAB group.…”
Section: Discussionsupporting
confidence: 94%
“…The MIDCAB group experienced fewer in-hospital stays, required fewer blood transfusions, and had a reduced incidence of cardiac-related events than their counterparts in the full sternotomy group. However, the reported results were not adjusted to baseline covariates ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study has the largest MIDCAB experience in the literature with a 20-year follow-up. [2][3][4][5][6] The survival results are similar not only to those reported in other MIDCAB studies, 5,6 but also to those reported for conventional coronary artery bypass via sternotomy and cardiopulmonary bypass. 7 Also encouraging was the lower revascularization rate for MIDCAB compared with PCI for proximal LAD disease (5.5% vs 20%-34%).…”
supporting
confidence: 83%
“…Thence, MIDCAB is considered a powerful option for the treatment of single-vessel coronary disease. 18 Recently published American guideline on ischemic heart disease recommended 2a PCI for the treatment of LAD or left main (LM) coronary artery disease, at which point MIDCAB may be beneficial for long-term survival and repeated revascularization. 19 The meta-analysis from Gianoli et al comparing MIDCAB and PCI revealed that PCI had a lower in-hospital mortality rate, whereas MIDCAB demonstrated superiority in terms of long-term survival and repeated revascularization.…”
Section: Palabras Clave: Cardiopatía Isquémica Cirugía Mínimamente In...mentioning
confidence: 99%